The effect of social capital on the career choice of entrepreneurship or employment in a closed ecosystem - Tang, Yong (Frontiers in Environmental Science, 2022)
In a closed eco-system, for the reason that the population is fixed, the career choice for individuals is highly impacted by the system’s employability and workability. This paper conducts some modifications for the model designed by Kihlstrom & Laffont (1979) to explore the career choice between entrepreneurship and employment in a closed eco-system and under the context of China. Taking social capital into K-L model, and adopting equilibrium analysis, the results show that: When social capital can only reduce the set-up cost for the entrepreneurship, there exists only one equilibrium point, and the higher social capital holders will choose entrepreneurship and the lower social capital holders will choose to be workers; When social capital can both reduce the set-up cost for the entrepreneurship and secure the worker’s job, there will appear at least 4 equilibrium points, and along with the strength of social capital (from the highest to the lowest), the staggered career choice is entrepreneurship, employment, entrepreneurship, employment and unemployment. Under both situations, there will appear Schumpeter effect. If social capital can be securing job, there will appear refugee effect.